Development of G-MAG Media on the Ability to Recognize the Concepts of Triangle and Square in Children Aged 5–6 Years - Fitriana, Novita; Widayati, Sri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Limited learning media for geometry often hinders early childhood in understanding basic shapes such as triangles and squares. To address this issue, G-MAG (Geometry Imagination) media was developed to strengthen the recognition and classification skills of children aged 5–6 years. The research applied the Research and Development (R&D) approach with the ADDIE model, involving 15 children at TK Khadijah, Surabaya. Data were obtained through observation and questionnaires, while the effectiveness test used the Wilcoxon Match Pairs Test. The media, consisting of a 35 × 8 cm geometry tower, color dice, and shape dice, was validated by experts and judged highly feasible. Effectiveness results indicated a significant improvement (Asymp. Sig (2-tailed) = 0.001 < 0.05) between pretest and posttest scores. Children showed better abilities in recognizing and classifying geometric forms through repeated play-based activities. G-MAG provides an engaging, meaningful learning experience and has potential for broader application in early childhood education.